Enhancing Career Pathways for Maritime Graduates through Human Resource Management Strategies - Abdul Rachman; Bambang Sumali; Susi Herawati; Firdaus Bintang Cahyanti; Devananda Vincensius Siregar; Junian Budi Argo (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research investigates how maritime vocational schools can enhance the career pathways of graduates by aligning educational outcomes with the needs of the maritime industry. Through qualitative analysis of perspectives from maritime professionals, lecturers, graduates, and government officers, the study identifies critical gaps in technology integration, environmental sustainability, and soft skills development. The research underscores the importance of industry collaboration, continuous learning, and adaptability in vocational education. By adopting human resource management strategies, schools can bridge the gap between education and industry, fostering stronger networks and preparing graduates for long-term success in a rapidly evolving maritime sector. The study emphasizes the role of internships, mentorships, and alumni networks in improving job placement and career advancement opportunities for maritime graduates. Keywords: , , ,